Aftershocks are fluid-driven and decay rates controlled by permeability dynamics - Stephen A. Miller (Nature Portfolio, 2020)
In this study, the authors propose that a fluid rich environment is necessary to generate long-lasting aftershock sequences. Based on this premise, the study presents a theory for modeling fluid-driven earthquake sequences